Mujer de 43 años con leves hipodensidades de la sustancia blanca subcortical - Ana Raquel Freitas; Heloísa Ribeiro (Sociedade Galega de Medicina Interna, 2018)
We present the case of a 43-year-old woman with history of unmedicated dyslipidemia, non-functioning thyroid nodules and arterial hypertension diagnosed for 5 years and controlled with angiotensin converting inhibitor therapy. She was admitted at the Emergency Department due to frontal headache lasting for 15 days associated with episodes of blurred vision with a few minutes of duration and vomiting in the previous day.